FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN KUNJUNGAN WISATA DI AGROWISATA KABUPATEN SEMARANG - DA, Sakti Nurani; Yuliawati, Yuliawati (JURNAL AGRIBISNIS TERPADU, 2018)
Industrial organizations that are increasing every year are one of the largest foreign exchange contributors industries. This study aims to find out visitor information and the factors that influence the visit decision. Free variables that provide accessibility, expenses, facilities, promotions, income, employment and education. The sampling method uses non probability sampling with a technique that is accidental sampling. The research sample was 40 agro-tourism visitors. Data collection using primary data in the form of questionnaires distributed to visitors and secondary data from the study literature on books, theses, journals and the internet. To identify factors related to decisions in SPSS 24. Characteristics of respondents in agro-tourism from women aged 26 to 35 years, originating from outside the agrotourism area, earning two million to three million and employment of civil servants with undergraduate and high school level. The results of the trial with ordinal logistic regression show that there are 4 variables that have a significant effect on the results of the task, namely accessibility, satisfaction, promotion and income.